Development of Plywood Media into a Magic Drawer to Improve the Cognitive of Children Aged 4-5 Years at Birrul Walidain Kindergarten Gondangrejo Pekalongan East Lampung - Agustiningsih Agustiningsih; Leli Fertiliana Dea; Ferdian Utama (CV. Creative Tugu Pena, 2025)
Birrul Walidain Gondangrejo Kindergarten, East Lampung, is an early childhood education institution that seeks to develop all aspects of child development, especially children's cognitive abilities through the use of concrete and interactive learning media. To optimize learning, it is necessary to add media with a new model so that the available teaching media is more maximal and varied. In this study, the